OPTIMASI pH DAN SUHU PADA AKTIVITAS ENZIM LIPASE DARI BIJI KAKAO (Theobroma cacao L.) BERKAPANG - Hutasoit, Novriyanti; Timur Ina, Putu; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This research was aimed to obtain lipase enzyme from mold of cacao beans and get optimum pH and temperature on lipase enzyme activity. The experimental design used Randomized Block Design (RBD) with different pH treatment as follows: pH 5, pH 6, pH 7, pH 8, and pH 9 and temperature treatment in a row as follows: 30 o C, 35 o C , 40 o C, 45 o C, and 50 o C. Each treatment was repeated three times to obtain 15 experimental units. Data were analyzed using analysis of variance, when data was effected and then continued with Duncan test. The result showed that pH treatment and temperature significantly influenced the activities of lipase enzyme. The highest lipase enzyme activity was obtained at pH 6 treatment which is 0.107 U/ml and in temperature 35 o C treatment 0.102 U/ml.
Keywords: Lipase enzyme, mold, cocoa beans